Ultrathin flexible self-supporting sodium metal negative electrode protection material as well as preparation method and application thereof

Through plasma enhanced chemical vapor deposition technology, ultra-thin flexible self-supported sodium metal negative electrode protection material was prepared, which solved the problems of dendrite growth, low utilization rate and poor interface compatibility of existing materials at large magnification, and achieved higher stable life and energy density.

CN119742471AActive Publication Date: 2025-04-01GUANGDONG UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411871805.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-04-01
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

The existing sodium metal negative electrode protection materials have problems such as dendrite growth, low material utilization, and poor interfacial compatibility at large ratio.

Method used

By using precursors such as methane, pyridine and sodium chloride, and using plasma-enhanced chemical vapor deposition technology, an ultra-thin flexible self-supporting sodium metal negative electrode protection material was prepared. The material has high conductivity, good morphology and excellent electrochemical properties.

Benefits of technology

The uniformity and thinness of the metal plating layer are achieved, the volume changes during the cycle are slowed down, and the surface micropores and gradient doping are combined to form a good conductive path, which improves the stable life of the energy storage device and increases the energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119742471A_ABST
    Figure CN119742471A_ABST
Patent Text Reader

Abstract

The invention discloses an ultrathin flexible self-supporting sodium metal negative electrode protection material as well as a preparation method and application thereof, and belongs to the technical field of electrochemical energy storage materials. The preparation method comprises the following steps: SO1, placing a precursor in a reactor, then placing the reactor in a deposition device, introducing a carbon source / nitrogen source for reaction, and cooling to room temperature after the reaction is finished to obtain a sample containing a salt template; and adding deionized water into the sample containing the salt template for soaking, and drying to obtain the ultrathin flexible self-supporting sodium metal negative electrode protection material. According to the ultrathin flexible self-supporting sodium metal negative electrode protection material disclosed by the invention, a metal coating can be more uniform and thinner, and volume change can be slowed down in a repeated circulation process; a good conductive path can be formed through mutual combination of surface micropores and gradient doping, ion / electron transfer is promoted, and the stable service life of the energy storage device is prolonged; the material is light, thin and high in utilization rate, thereby effectively improving energy density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrochemical energy storage materials, and in particular to an ultra-thin flexible self-supporting sodium metal negative electrode protection material and a preparation method and application thereof. Background Art

[0002] Over the past few decades, lithium-ion batteries have become the most common power source in the portable electronics market. However, due to the global shortage of lithium resources and the increase in widespread market demand, the high cost of lithium resources has led to extensive research and development of rechargeable batteries with high energy density and long cycle life. Sodium metal is an excellent alternative due to its high theoretical specific capacity (1166 mAh g -1 ) and low standard electrode potential (-2.71Vvs. standard hydrogen electrode, SHE), as well as because of its lower cost and higher natural abundance. However, similar to lithium metal anodes, the development of sodium metal anodes has been hindered by some serious problems. First, uneven deposition can lead to severe dendrite growth during cycling, and sodium dendrites close to active sites may dissolve rapidly and unevenly, causing them to separate from the substrate, producing "dead sodium" and causing battery short-circuit problems. Second, due to the high electrochemical activity of metallic sodium and the repeated expansion and contraction of metallic sodium during electrochemical cycling, the solid electrolyte interface (SEI) between the sodium metal anode and the electrolyte is easily decomposed, resulting in side reactions between the electrolyte and the newly exposed metal. The side reactions will continue to deplete the electrolyte and sodium metal, which is an irreversible reaction, accompanied by the thickening of the SEI layer, resulting in a significant decrease in the electrochemical performance of sodium metal batteries.

[0003] In order to solve the above problems, researchers have developed a series of optimization methods for metal anodes. Among them, carbon-based carriers have attracted much attention due to their high chemical stability, good mechanical properties and strong conductivity. Researchers mainly optimize carbon structures from the following aspects.

[0004] 1) Precisely adjust the surface structure of carbon at a scale below the critical nucleation size: Photolithography, template flash etching and laser micromachining have been used to obtain patterned holes, grooves or vertically arranged microchannels, but it is difficult to work at the nanoscale. 2) Construct a three-dimensional carrier: Three-dimensional conductive / sodium-philic carriers can partially alleviate the problems of sodium dendrite growth and volume expansion compared to traditional two-dimensional carriers. However, metal deposition on three-dimensional carriers often presents a "top growth" mode. 3) Protective layer: As a physical barrier to hinder dendrite growth, its interfacial compatibility is more complex. Designing multifunctional carbon materials will increase the thickness, sacrificing volume and mass energy density.

[0005] Therefore, it is necessary to prepare carbon materials that meet the requirements of gradient doping of heteroatoms, limiting the size of metal crystal cores, refining the protective layer, and being light and thin, and apply them in electrochemical energy storage devices. Summary of the invention

[0006] Based on this, the embodiment of the present invention provides an ultra-thin flexible self-supporting sodium metal negative electrode protection material and its preparation method and application. It aims to solve the problems of existing sodium metal negative electrode protection materials such as dendrite growth at high rates, low material utilization, and poor interface compatibility. The preparation method adopted by the present invention uses methane, pyridine and sodium chloride to prepare an ultra-thin flexible self-supporting sodium metal negative electrode protection material with high conductivity, good morphology and excellent electrochemical performance through rapid reaction.

[0007] The purpose of the present invention is achieved through the following technical solutions:

[0008] On the one hand, an embodiment of the present invention provides a method for preparing an ultra-thin flexible self-supporting sodium metal negative electrode protection material, comprising the following steps:

[0009] SO1, placing the precursor in a reactor, then placing the reactor in a deposition device, introducing a carbon source / nitrogen source for reaction, and cooling to room temperature after the reaction to obtain a sample containing a salt template;

[0010] SO2. Take out the sample of the salt template in step S01, and add deionized water to the sample of the salt template for soaking; dry it after soaking to obtain an ultra-thin flexible self-supporting sodium metal negative electrode protection material.

[0011] As a preferred embodiment, in step SO1,

[0012] The precursor is sodium chloride. By controlling different reaction temperatures, sodium chloride crystals of different sizes can be obtained after recrystallization, which is low in cost and easy to obtain.

[0013] The amount of the precursor volume is 2.5 g. Further preferably, the precursor is piled into a hillock and placed in the reactor.

[0014] The reactor is a silicon wafer placed on a corundum ark; the deposition device is a plasma enhanced chemical vapor deposition device.

[0015] The carbon source / nitrogen source is a carbon-containing gas and a volatile liquid containing carbon and nitrogen elements; wherein the carbon-containing gas is preferably a hydrogen mixed gas with a methane volume content of 30%, and the volatile liquid containing carbon and nitrogen elements is one of pyridine or acetonitrile or a mixture of at least two of them.

[0016] The volatile liquid containing carbon and nitrogen elements is both a carbon source and a dopant; the volatile liquid containing carbon and nitrogen elements is contained in an external liquid bottle.

[0017] In the reaction process of introducing the carbon source, the carbon-containing gas is introduced first, then the carbon-containing gas is turned off and the volatile liquid containing carbon and nitrogen is introduced. Further preferably, the carbon-containing gas is reacted for 10 minutes at a flow rate of 150 sccm, the carbon-containing gas is turned off, and the volatile liquid containing carbon and nitrogen is introduced with a flow rate of 5 sccm to 15 sccm (see the example operation steps for the specific control process).

[0018] The initial temperature of the reaction is 20°C, the reaction temperature of the reaction is 650°C to 900°C, the heating rate is 10°C / min, and the temperature is then reduced to 300°C.

[0019] The reaction time is 90 min to 120 min (including heating time and deposition time).

[0020] Further preferably, the initial temperature of the reaction is 20°C, and the reaction temperature of the reaction is: heating furnace temperature: 650°C~900°C (plasma power: 400w~500w) for 10-15min; the temperature is reduced to 300°C (plasma power: 150w) for 12min-22min.

[0021] The cooling method is to remove the heating device after the reaction is completed, and allow the sample to cool down quickly to room temperature.

[0022] As a preferred embodiment, in step SO2,

[0023] The amount of deionized water used is 70 ml. The residual salt template in the reaction process can be removed by soaking in deionized water.

[0024] The soaking time is 24 hours.

[0025] The immersion was carried out in a culture dish with a diameter of 20 cm.

[0026] The soaking and cleaning was performed twice.

[0027] The drying temperature is 60° C., and the drying time is 1 h.

[0028] The drying is preferably carried out in an electric heated forced air drying oven.

[0029] On the other hand, an embodiment of the present invention also provides an ultra-thin flexible self-supporting sodium metal negative electrode protection material obtained by the above preparation method.

[0030] On the other hand, the ultra-thin flexible self-supporting sodium metal negative electrode protection material is used in sodium metal batteries.

[0031] Compared with the prior art, this application has the following technical effects:

[0032] The ultra-thin flexible self-supporting sodium metal negative electrode protection material obtained by plasma vapor evaporation deposition in the present application has a smooth surface and an internal interconnected unit structure. The small-sized interconnected unit limits the critical nucleation size, making the metal coating more uniform and thin, slowing down the volume change during the cycle. At the same time, the surface micropore size limits the entry of solvent molecules into the material, reducing the occurrence of side reactions; combined with gradient nitrogen doping, it is conducive to the formation of a good conductive path, promoting the transfer of ions / electrons and increasing the stable life of the energy storage device. Compared with the traditional electrode made by brushing and filtration, the prepared flexible self-supporting carbon film is thinner and has a higher utilization rate, thereby effectively improving the energy density. At the same time, the multifunctional integrated flexible self-supporting carbon film can overcome the problem of single function of other carbon carriers. The preparation method of the present application is simple, low-cost, and can be suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0034] Figure 1 SEM and TEM characterization images of the ultra-thin flexible self-supporting sodium metal negative electrode protection material provided in Example 1;

[0035] Figure 2 SEM and TEM characterization images of the ultra-thin flexible self-supporting sodium metal negative electrode protection material provided in Example 2;

[0036] Figure 3 SEM and TEM characterization images of the ultra-thin flexible self-supporting sodium metal negative electrode protection material provided in Example 3;

[0037] Figure 4 The sodium metal symmetric battery prepared in Example 3 is 8 mA·cm -2 Cyclic performance test diagram under 100% discharge depth;

[0038] Figure 5 TEM characterization image and BET test data of the surface flakes in the ultra-thin flexible self-supporting sodium metal negative electrode protection material provided in Examples 3 and 4;

[0039] Figure 6 This is a cross-sectional SEM characterization image of the ultra-thin flexible self-supporting sodium metal negative electrode protection material provided in Example 5;

[0040] Figure 7 This is a cross-sectional SEM characterization image of the ultra-thin flexible self-supporting sodium metal negative electrode protection material provided in Example 6.

[0041] Figure 8 This is a cross-sectional SEM characterization image of the ultra-thin flexible self-supporting sodium metal negative electrode protection material obtained in Example 3.

[0042] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0043] The technical solutions in the embodiments of the present invention will be described clearly and completely below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] It should be noted that if the embodiments of the present invention involve directional indications (such as up, down, left, right, front, back, top, bottom...), the directional indications are only used to explain the relative position relationship, movement status, etc. between the components in a certain specific posture. If the specific posture changes, the directional indication will also change accordingly.

[0045] In this application, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0046] It should be noted that when an element is referred to as being "fixed to" or "disposed on" another element, it may be directly on the other element or there may be an intermediate element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be an intermediate element at the same time.

[0047] In addition, if there are descriptions involving "first", "second", etc. in the embodiments of the present invention, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or suggesting their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in the field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0048] The ultra-thin flexible self-supporting sodium metal negative electrode protection material prepared by the present application can not only make the metal coating more uniform and thin, but also slow down the volume change during repeated cycles; it can also form a good conductive path through the combination of surface micropores and gradient doping, promote the transfer of ions / electrons and increase the stable life of energy storage devices; the material is light and thin and has a higher utilization rate, thereby effectively improving the energy density. At the same time, the multifunctional integrated flexible self-supporting carbon film can overcome the problem of single function of other carbon carriers.

[0049] To achieve the above objectives, on the one hand, an embodiment of the present invention provides a method for preparing an ultra-thin flexible self-supporting sodium metal negative electrode protection material, comprising the following steps:

[0050] SO1, placing the precursor in a reactor, then placing the reactor in a deposition device, introducing a carbon source / nitrogen source for reaction, and cooling to room temperature after the reaction to obtain a sample containing a salt template;

[0051] SO2. Take out the sample of the salt template in step S01, and add deionized water to the sample of the salt template for soaking; dry it after soaking to obtain an ultra-thin flexible self-supporting sodium metal negative electrode protection material.

[0052] As a preferred embodiment, in step SO1,

[0053] The precursor is sodium chloride. By controlling different reaction temperatures, sodium chloride crystals of different sizes can be obtained after recrystallization. The precursor is low in cost and easy to obtain.

[0054] The amount of the precursor volume is 2.5 g. The precursor is piled into a hillock and placed in the reactor.

[0055] The reactor is a silicon wafer placed on a corundum ark; the deposition device is a plasma enhanced chemical vapor deposition device. In a vacuum oxygen-free environment, the two processes of plasma bombardment and high-temperature evaporation are carried out simultaneously in the deposition device. The carbon source / nitrogen source is cracked into high-energy carbon / nitrogen atoms after being bombarded by a high-energy plasma beam. The precursor evaporates into a gaseous state at high temperature and reaches a low-temperature zone, then combines with high-energy carbon atoms / nitrogen atoms and is deposited on the silicon wafer.

[0056] The carbon source / nitrogen source is a gas containing carbon elements and a volatile liquid containing carbon and nitrogen elements; wherein the gas containing carbon elements is preferably a hydrogen mixed gas with a flow rate of 150sccm and a methane volume content of 30%, and the volatile liquid containing carbon and nitrogen elements is one of pyridine or acetonitrile.

[0057] The volatile liquid containing carbon and nitrogen elements is both a carbon source and a dopant; the volatile liquid containing carbon and nitrogen elements is contained in an external liquid bottle. During the reaction process of introducing the carbon source, the gas containing carbon elements is introduced first for a period of time and then the volatile liquid containing carbon elements is introduced.

[0058] In SO1, the carbon-containing gas was reacted at a flow rate of 150 sccm for 10 min, and then closed and a volatile liquid containing carbon was introduced at a flow rate of 5 sccm to 15 sccm.

[0059] The initial temperature of the reaction is 20°C, the reaction temperature of the reaction: the heating furnace temperature is 650°C to 900°C (plasma power: 400w to 500w), the heating rate is 10°C / min, and the temperature is then reduced to 300°C.

[0060] The reaction time is 90 min to 120 min (including heating time and deposition time).

[0061] Further preferably, the initial temperature of the reaction is 20°C, and the reaction temperature of the reaction is: heating furnace temperature: 650°C~900°C (plasma power: 400w~500w) for 10-15min; the temperature is reduced to 300°C (plasma power: 150w) for 12min-22min.

[0062] The cooling method is to remove the heating device after the reaction is completed, and allow the sample to cool down quickly to room temperature.

[0063] As a preferred embodiment, in step SO2,

[0064] The amount of deionized water used is 70 ml. The residual salt template in the reaction process can be removed by soaking in deionized water.

[0065] The soaking time is 24 hours.

[0066] The immersion was carried out in a culture dish with a diameter of 20 cm.

[0067] The soaking and cleaning was performed twice.

[0068] The drying temperature is 60° C., and the drying time is 1 h.

[0069] The drying is preferably carried out in an electric heated forced air drying oven.

[0070] On the other hand, an embodiment of the present invention also provides an ultra-thin flexible self-supporting sodium metal negative electrode protection material obtained by the above preparation method.

[0071] Another invention is that the ultra-thin flexible self-supporting sodium metal negative electrode protection material can be applied to sodium metal batteries.

[0072] The ultra-thin flexible self-supporting sodium metal negative electrode protection material prepared by the present application can not only make the metal coating more uniform and thin, but also slow down the volume change during repeated cycles; it can also form a good conductive path through the combination of surface micropores and gradient doping, promote the transfer of ions / electrons and increase the stable life of energy storage devices; the material is light and thin and has a higher utilization rate, thereby effectively improving the energy density. At the same time, the multifunctional integrated flexible self-supporting carbon film can overcome the problem of single function of other carbon carriers.

[0073] Example 1

[0074] A method for preparing an ultra-thin flexible self-supporting sodium metal negative electrode protection material comprises the following steps:

[0075] SO1, placing the precursor in a reactor, then placing the reactor in a deposition device, introducing a carbon source / nitrogen source for reaction, and cooling to room temperature after the reaction to obtain a sample containing a salt template;

[0076] SO2. Take out the sample of the salt template in step S01, and add deionized water to the sample of the salt template for soaking; dry it after soaking to obtain an ultra-thin flexible self-supporting sodium metal negative electrode protection material.

[0077] In step SO1,

[0078] The precursor is sodium chloride.

[0079] The amount of the precursor used is 2.5 g.

[0080] The reactor is a silicon wafer placed on a square corundum boat; the deposition device is a plasma enhanced chemical vapor deposition device.

[0081] The carbon source / nitrogen source is a hydrogen mixed gas with a methane volume content of 30% and a volatile liquid pyridine containing carbon and nitrogen elements.

[0082] The carbon-containing gas was reacted for 10 minutes at a flow rate of 150 sccm, and then closed and volatile liquid pyridine containing carbon and nitrogen elements was introduced with a flow rate changed from 5 sccm to 15 sccm (controlled by a gas flow meter to increase by 0.59 sccm / min).

[0083] The initial temperature of the reaction is 20°C, and the reaction temperature of the reaction is: the heating furnace temperature is 650°C, the plasma power is 400w, and the heating rate is 10°C / min; during the deposition process, 650°C is maintained for 10min, and then the temperature is reduced to 300°C, and the plasma power is 150w for 17min.

[0084] The reaction time is 90 min (including heating time and deposition time).

[0085] The cooling method is to remove the heating device after the reaction is completed, and allow the sample to cool down quickly to room temperature.

[0086] In step SO2,

[0087] The amount of deionized water used is 70 ml. The residual salt template in the reaction process can be removed by soaking in deionized water.

[0088] The soaking time is 24 hours.

[0089] The immersion was carried out in a culture dish with a diameter of 20 cm.

[0090] The soaking and cleaning was performed twice.

[0091] The drying temperature is 60° C., and the drying time is 1 h.

[0092] The drying is preferably carried out in an electric heated forced air drying oven.

[0093] Figure 1 This is a SEM characterization image of the ultra-thin flexible self-supporting sodium metal negative electrode protection material obtained in Example 1; Figure 1 It can be observed that the surface of the negative electrode material is a layer of uniform flakes, and the interior is an interconnected structure with a unit size of ~1 micron.

[0094] Example 2

[0095] A method for preparing an ultra-thin flexible self-supporting sodium metal negative electrode protection material comprises the following steps:

[0096] SO1, placing the precursor in a reactor, then placing the reactor in a deposition device, introducing a carbon source / nitrogen source for reaction, and cooling to room temperature after the reaction to obtain a sample containing a salt template;

[0097] SO2. Take out the sample of the salt template in step S01, and add deionized water to the sample of the salt template for soaking; dry it after soaking to obtain an ultra-thin flexible self-supporting sodium metal negative electrode protection material.

[0098] In step SO1,

[0099] The precursor is sodium chloride.

[0100] The amount of the precursor used is 2.5 g.

[0101] The reactor is a silicon wafer placed on a square corundum boat; the deposition device is a plasma enhanced chemical vapor deposition device.

[0102] The carbon source is a hydrogen mixed gas with a methane volume content of 30% and a volatile liquid pyridine containing carbon and nitrogen elements.

[0103] The carbon-containing gas was reacted for 10 minutes at a flow rate of 150 sccm, and then closed and a volatile liquid containing carbon and nitrogen was introduced with a flow rate changed from 5 sccm to 15 sccm (controlled by a gas flow meter to increase by 0.59 sccm / min).

[0104] The initial temperature of the reaction is 20°C, and the reaction temperature of the reaction is: the heating furnace temperature is 800°C, the plasma power is 400w, and the heating rate is 10°C / min; during the deposition process, 800°C is maintained for 10min, and then the temperature is reduced to 300°C, and the plasma power is 150w for 17min.

[0105] The reaction time is 105 min (including heating time and deposition time).

[0106] The cooling method is to remove the heating device after the reaction is completed, and allow the sample to cool down quickly to room temperature.

[0107] In step SO2,

[0108] The amount of deionized water used is 70 ml. The residual salt template in the reaction process can be removed by soaking in deionized water.

[0109] The soaking time is 24 hours.

[0110] The immersion was carried out in a culture dish with a diameter of 20 cm.

[0111] The soaking and cleaning was performed twice.

[0112] The drying temperature is 60° C., and the drying time is 1 h.

[0113] The drying is preferably carried out in an electric heated forced air drying oven.

[0114] Figure 2 This is a SEM characterization image of the ultra-thin flexible self-supporting sodium metal negative electrode protection material obtained in Example 2; Figure 2 It can be observed that the surface of the negative electrode material is a layer of uniform flakes, and the interior is an interconnected structure with a unit size of ~200 nanometers.

[0115] Example 3

[0116] A method for preparing an ultra-thin flexible self-supporting sodium metal negative electrode protection material comprises the following steps:

[0117] SO1, placing the precursor in a reactor, then placing the reactor in a deposition device, introducing a carbon source / nitrogen source for reaction, and cooling to room temperature after the reaction to obtain a sample containing a salt template;

[0118] SO2. Take out the sample of the salt template in step S01, and add deionized water to the sample of the salt template for soaking; dry it after soaking to obtain an ultra-thin flexible self-supporting sodium metal negative electrode protection material.

[0119] In step SO1,

[0120] The precursor is sodium chloride.

[0121] The amount of the precursor used is 2.5 g.

[0122] The reactor is a silicon wafer placed on a square corundum boat; the deposition device is a plasma enhanced chemical vapor deposition device.

[0123] The carbon source is a hydrogen mixed gas with a methane volume content of 30% and a volatile liquid pyridine containing carbon and nitrogen elements.

[0124] The carbon-containing gas was reacted for 10 minutes at a flow rate of 150 sccm, and then closed and a volatile liquid containing carbon and nitrogen was introduced with a flow rate changed from 5 sccm to 15 sccm (controlled by a gas flow meter to increase by 0.59 sccm / min).

[0125] The initial temperature of the reaction is 20°C, and the reaction temperature of the reaction is: the heating furnace temperature is 900°C, the plasma power is 400w, and the heating rate is 10°C / min; during the deposition process, 900°C is maintained for 10min, and then the temperature is reduced to 300°C, and the plasma power is 150w for 17min.

[0126] The reaction time is 115 min (including heating time and deposition time).

[0127] The cooling method is to remove the heating device after the reaction is completed, and allow the sample to cool down quickly to room temperature.

[0128] In step SO2,

[0129] The amount of deionized water used is 70 ml. The residual salt template in the reaction process can be removed by soaking in deionized water.

[0130] The soaking time is 24 hours.

[0131] The immersion was carried out in a culture dish with a diameter of 20 cm.

[0132] The soaking and cleaning was performed twice.

[0133] The drying temperature is 60° C., and the drying time is 1 h.

[0134] The drying is preferably carried out in an electric heated forced air drying oven.

[0135] The self-supporting carbon film prepared in Example 3 was cut into a size of 10 mm as an electrode and pre-deposited with 4 mAh·cm -2 Sodium metal; sodium hexafluorophosphate NaPF6 as solute, dimethyl carbonate DME as solvent, prepared at a concentration of 1 mol L -1 The solution was used as the electrolyte; finally, a 2032 button-type sodium metal symmetric battery was assembled and the charge and discharge test was carried out, and the test voltage window was 0.01V-3V.

[0136] Figure 3 The SEM and TEM characterization images of the ultra-thin flexible self-supporting sodium metal negative electrode protection material obtained in Example 3; Figure 3 It can be observed that the surface of the negative electrode material is a layer of uniform flakes, and the interior is an interconnected structure with a unit size of ~50 nanometers.

[0137] Figure 4 The sodium metal symmetric battery prepared in Example 3 has a high current of 8 mA·cm -2 Cyclic performance test diagram under 100% discharge depth, from Figure 4 It can be seen that after 1300 cycles, it still exhibits a low hysteresis voltage of 41.9 mV, showing good cycle stability.

[0138] Example 4

[0139] A method for preparing an ultra-thin flexible self-supporting sodium metal negative electrode protection material comprises the following steps:

[0140] SO1, placing the precursor in a reactor, then placing the reactor in a deposition device, introducing a carbon source / nitrogen source for reaction, and cooling to room temperature after the reaction to obtain a sample containing a salt template;

[0141] SO2. Take out the sample of the salt template in step S01, and add deionized water to the sample of the salt template for soaking; dry it after soaking to obtain an ultra-thin flexible self-supporting sodium metal negative electrode protection material.

[0142] In step SO1,

[0143] The precursor is sodium chloride.

[0144] The amount of the precursor used is 2.5 g.

[0145] The reactor is a silicon wafer placed on a square corundum boat; the deposition device is a plasma enhanced chemical vapor deposition device.

[0146] The carbon source is a hydrogen mixed gas with a methane volume content of 30% and a volatile liquid pyridine containing carbon and nitrogen elements.

[0147] The carbon-containing gas was reacted for 10 minutes at a flow rate of 150 sccm, and then closed and a volatile liquid containing carbon and nitrogen was introduced with a flow rate changed from 5 sccm to 15 sccm (controlled by a gas flow meter to increase by 0.59 sccm / min).

[0148] The initial temperature of the reaction is 20°C, and the reaction temperature of the reaction is: the heating furnace temperature is 900°C, the plasma power is 500w, and the heating rate is 10°C / min; during the deposition process, 900°C is maintained for 10min, and then the temperature is reduced to 300°C, and the plasma power is 150w for 17min.

[0149] The reaction time is 115 min (including heating time and deposition time).

[0150] The cooling method is to remove the heating device after the reaction is completed, and allow the sample to cool down quickly to room temperature.

[0151] In step SO2,

[0152] The amount of deionized water used is 70 ml. The residual salt template in the reaction process can be removed by soaking in deionized water.

[0153] The soaking time is 24 hours.

[0154] The immersion was carried out in a culture dish with a diameter of 20 cm.

[0155] The soaking and cleaning was performed twice.

[0156] The drying temperature is 60° C., and the drying time is 1 h.

[0157] The drying is preferably carried out in an electric heated forced air drying oven.

[0158] Figure 5 TEM characterization diagram of the surface flakes in the ultra-thin flexible self-supporting sodium metal negative electrode protection material obtained in Examples 3 and 4 and its corresponding BET test data; Figure 5 It can be observed that the pore size of the surface material can be controlled by controlling the plasma power.

[0159] Example 5

[0160] A method for preparing an ultra-thin flexible self-supporting sodium metal negative electrode protection material comprises the following steps:

[0161] SO1, placing the precursor in a reactor, then placing the reactor in a deposition device, introducing a carbon source / nitrogen source for reaction, and cooling to room temperature after the reaction to obtain a sample containing a salt template;

[0162] SO2. Take out the sample of the salt template in step S01, and add deionized water to the sample of the salt template for soaking; dry it after soaking to obtain an ultra-thin flexible self-supporting sodium metal negative electrode protection material.

[0163] In step SO1,

[0164] The precursor is sodium chloride.

[0165] The amount of the precursor used is 2.5 g.

[0166] The reactor is a silicon wafer placed on a square corundum boat; the deposition device is a plasma enhanced chemical vapor deposition device.

[0167] The carbon source is a hydrogen mixed gas with a methane volume content of 30% and a volatile liquid pyridine containing carbon and nitrogen elements.

[0168] The carbon-containing gas was reacted for 10 minutes at a flow rate of 150 sccm, and then closed and a volatile liquid containing carbon and nitrogen was introduced with a flow rate changed from 5 sccm to 15 sccm (controlled by a gas flow meter to increase by 0.83 sccm / min).

[0169] The initial temperature of the reaction is 20°C, and the reaction temperature of the reaction is: the heating furnace temperature is 900°C, the plasma power is 400w, and the heating rate is 10°C / min; during the deposition process, 900°C is maintained for 10 minutes, and then the temperature is reduced to 300°C for 12 minutes.

[0170] The reaction time is 100 min (including heating time and deposition time).

[0171] The cooling method is to remove the heating device after the reaction is completed, and allow the sample to cool down quickly to room temperature.

[0172] In step SO2,

[0173] The amount of deionized water used is 70 ml. The residual salt template in the reaction process can be removed by soaking in deionized water.

[0174] The soaking time is 24 hours.

[0175] The immersion was carried out in a culture dish with a diameter of 20 cm.

[0176] The soaking and cleaning was performed twice.

[0177] The drying temperature is 60° C., and the drying time is 1 h.

[0178] The drying is preferably carried out in an electric heated forced air drying oven.

[0179] Figure 6 The cross-sectional SEM characterization image and optical photograph of the ultra-thin flexible self-supporting sodium metal negative electrode protection material obtained in Example 5 have a thickness of 5 microns.

[0180] Example 6

[0181] A method for preparing an ultra-thin flexible self-supporting sodium metal negative electrode protection material comprises the following steps:

[0182] SO1, placing the precursor in a reactor, then placing the reactor in a deposition device, introducing a carbon source / nitrogen source for reaction, and cooling to room temperature after the reaction to obtain a sample containing a salt template;

[0183] SO2. Take out the sample of the salt template in step S01, and add deionized water to the sample of the salt template for soaking; dry it after soaking to obtain an ultra-thin flexible self-supporting sodium metal negative electrode protection material.

[0184] In step SO1,

[0185] The precursor is sodium chloride.

[0186] The amount of the precursor used is 2.5 g.

[0187] The reactor is a silicon wafer placed on a square corundum boat; the deposition device is a plasma enhanced chemical vapor deposition device.

[0188] The carbon source is a hydrogen mixed gas with a methane volume content of 30% and a volatile liquid pyridine containing carbon and nitrogen elements.

[0189] The carbon-containing gas was reacted for 10 minutes at a flow rate of 150 sccm, and then closed and a volatile liquid containing carbon and nitrogen was introduced with a flow rate changed from 5 sccm to 15 sccm (controlled by a gas flow meter to increase by 0.45 sccm / min).

[0190] The initial temperature of the reaction is 20°C, and the reaction temperature of the reaction is: the heating furnace temperature is 900°C, the plasma power is 400w, and the heating rate is 10°C / min; during the deposition process, 900°C is maintained for 10min, and then the temperature is reduced to 300°C, and the plasma power is 150w for 22min.

[0191] The reaction time is 120 min (including heating time and deposition time).

[0192] The cooling method is to remove the heating device after the reaction is completed, and allow the sample to cool down quickly to room temperature.

[0193] In step SO2,

[0194] The amount of deionized water used is 70 ml. The residual salt template in the reaction process can be removed by soaking in deionized water.

[0195] The soaking time is 24 hours.

[0196] The immersion was carried out in a culture dish with a diameter of 20 cm.

[0197] The soaking and cleaning was performed twice.

[0198] The drying temperature is 60° C., and the drying time is 1 h.

[0199] The drying is preferably carried out in an electric heated forced air drying oven.

[0200] Figure 7 The cross-sectional SEM characterization image and optical photograph of the ultra-thin flexible self-supporting sodium metal negative electrode protection material obtained in this Example 6 have a thickness of 15 microns.

[0201] Figure 8 The cross-sectional SEM characterization image and optical photograph of the ultra-thin flexible self-supporting sodium metal negative electrode protection material obtained in this Example 3 have a thickness of 10 microns.

[0202] Comparative Example 1

[0203] A method for preparing ordered mesoporous graphene (OMG) in this comparative example comprises the following steps:

[0204] (1) Preparation of graphene oxide (GO) aqueous solution: GO aqueous solution was prepared by the modified Hummers method and then redispersed in deionized water with a concentration of about 4 mg mL -1 ;

[0205] (2) Synthesis of oleic acid iron complex: 7.62 g of sodium oleate was dissolved in 150 mL of water, stirred for 1 h, and then 2.26 g of FeCl3·6H2O was added to prepare oleic acid iron complex;

[0206] (3) Preparation of precursor: 0.42 g or 0.21 g of suspended GO was added to the iron oleate complex solution, stirred until uniformly dispersed, and then freeze-dried;

[0207] (4) Calcination treatment: The obtained iron oleate / GO powder was heated to 500 °C in a furnace and calcined for 2 h under an argon (Ar) flow (flow rate of 100 sccm), or calcined under an Ar / H2 atmosphere (flow rates of 100 sccm / 30 sccm, respectively);

[0208] (5) Template removal: Fe3O4 nanoparticles were removed with hydrochloric acid (HCl), and then washed with water and ethanol three times respectively to obtain ordered mesoporous graphene (OMG).

[0209] The method of the present invention is compared with Comparative Example 1: The synthesis steps of Comparative Example 1 are cumbersome, and multiple steps of precursor synthesis are required, followed by a long calcination treatment to obtain a carbon material with small-sized interconnected units. Longer reaction time and more complex synthesis steps lead to more influencing factors, which limit the application of this method to a certain extent. The method of the present invention can quickly synthesize materials in one step, and use temperature changes to achieve template control of the size of the interconnected units. Under relatively simple synthesis steps, the reaction time is shorter, the energy consumption is lower, it is safe and convenient, and can be used to quickly prepare ultra-thin flexible self-supporting sodium metal negative electrode protection materials, with higher universality.

[0210] Comparative Example 2

[0211] The preparation method of a 3D carbon skeleton (CMFS) with "gradient sodium affinity" property in this comparative example comprises the following steps:

[0212] 1. Preparation of sodium-philic carbon fiber skeleton (CFS)

[0213] (1) First, the purchased bacterial cellulose (BC) was soaked in deionized water and ultrasonically cleaned for 1 hour.

[0214] (2) Then, the deionized water was replaced with ethanol and ultrasonic cleaning was performed again for 1 hour.

[0215] (3) It was then soaked in deionized water for 24 h, after which dry BC was obtained by freeze drying.

[0216] The dried BC was cut into discs with a diameter of 19 mm, and several pieces were placed in a corundum boat and transferred to a tube furnace. In an argon atmosphere, it was heated to 700°C at a heating rate of 3°C / min and carbonized for 2 hours. The obtained three-dimensional carbon fiber skeleton was named CFS.

[0217] 2. Preparation of "gradient sodium affinity" support (CMFS)

[0218] (1) A 40-fold concentrated polytetrafluoroethylene (PTFE) dispersion (60 wt.%) was added dropwise to the CFS surface and allowed to stand for half an hour to allow it to be completely wetted by PTFE.

[0219] (2) Then the PTFE-impregnated CFS was annealed again at 700°C for 1 hour at a heating rate of 3°C / min in an argon atmosphere to obtain a three-dimensional carbon microsphere interwoven fiber skeleton, which is CMFS. After carbonization, the diameter of CFS and CMFS was 14 mm.

[0220] The method of the present invention is compared with Comparative Example 2: the synthesis steps of Comparative Example 2 are cumbersome, and the original material needs to be prepared and then reacted to achieve the purpose of gradient nitrogen doping. However, the method of the present invention can quickly synthesize a gradient-doped three-dimensional interconnected structure in one step, and the nitrogen doping amount is controlled by adjusting the pyridine flow rate, thereby improving the stability of the carbon network and effectively simplifying the steps of preparing a gradient-doped high-performance three-dimensional carbon carrier.

[0221] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing an ultra-thin flexible self-supporting sodium metal negative electrode protection material, characterized in that: The steps include: SO1, placing the precursor in a reactor, then placing the reactor in a deposition device, introducing a carbon source / nitrogen source for reaction, and cooling to room temperature after the reaction to obtain a sample containing a salt template; SO2. Take out the sample of the salt template in step S01, and add deionized water to the sample of the salt template for soaking; dry it after soaking to obtain an ultra-thin flexible self-supporting sodium metal negative electrode protection material.

2. The method for preparing the ultra-thin flexible self-supporting sodium metal negative electrode protection material according to claim 1, characterized in that: In step SO1, The precursor is sodium chloride; The amount of the precursor volume is 2.5g; The precursor is piled into a hillock and placed in the reactor.

3. The method for preparing the ultra-thin flexible self-supporting sodium metal negative electrode protection material according to claim 1, characterized in that: In step SO1, The carbon source / nitrogen source is a carbon-containing gas and a volatile liquid containing carbon and nitrogen elements; wherein the carbon-containing gas is a hydrogen mixed gas with a methane volume content of 30%, and the volatile liquid containing carbon and nitrogen elements is one of pyridine or acetonitrile or a mixture of at least two of them.

4. The method for preparing the ultra-thin flexible self-supporting sodium metal negative electrode protection material according to claim 3, characterized in that: In step SO1, the carbon-containing gas is reacted at a flow rate of 150 sccm for 10 min, the carbon-containing gas is turned off, and a volatile liquid containing carbon and nitrogen is introduced at a flow rate of 5 sccm to 15 sccm.

5. The method for preparing the ultra-thin flexible self-supporting sodium metal negative electrode protection material according to claim 1, characterized in that: In step SO1, the initial temperature of the reaction is 20°C, the reaction temperature of the reaction is 650°C to 900°C, the heating rate is 10°C / min, and the temperature is then reduced to 300°C; The reaction time is 90 min to 120 min.

6. The method for preparing the ultra-thin flexible self-supporting sodium metal negative electrode protection material according to claim 1, characterized in that: In step SO1, the initial temperature of the reaction is 20°C, and the reaction temperature of the reaction is: heating furnace temperature: 650°C to 900°C for 10-15 minutes; the temperature is reduced to 300°C for 12 minutes to 22 minutes.

7. The method for preparing the ultra-thin flexible self-supporting sodium metal negative electrode protection material according to claim 1, characterized in that: In step SO1, The reactor is a silicon wafer placed on a corundum ark; the deposition device is a plasma enhanced chemical vapor deposition device; The cooling method is to remove the heating device after the reaction is completed, and allow the sample to cool down quickly to room temperature.

8. The method for preparing the ultra-thin flexible self-supporting sodium metal negative electrode protection material according to claim 1, characterized in that: In step SO2, The amount of deionized water is 70 ml; The soaking time is 24h; The drying temperature is 60°C and the drying time is 1h; The drying is carried out in an electric heated air drying oven.

9. An ultra-thin flexible self-supporting sodium metal negative electrode protection material, characterized in that: Obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the ultra-thin flexible self-supporting sodium metal negative electrode protection material according to claim 9 in sodium metal batteries.

Citation Information

Patent Citations

  • Battery self-supporting hierarchical structure material as well as preparation method and application thereof

    CN112331850A

  • Preparation method of flexible self-supporting iron-doped porous carbon nanofiber lithium metal negative electrode framework material

    CN113921768A

  • Sodium metal negative electrode current collector and preparation method and application thereof

    CN117996087A

  • Carbon-based composite material, preparation method therefor, and application thereof

    US20230147642A1